Sacred Body: Readings in Jewish Literary Illumination - Sabbath, Roberta Sterman (Lexington Books, 2023)
Sacred Body: Readings in Jewish Literary Illumination provides fresh and insightful interpretations of Jewish texts, narratives, and cultural practices that show how these artifacts unhinge the “sacred” from the divine and focus instead on the “everyday sacred” of a dynamic earthly existence that emphasizes the body, celebrates life-affirming decisions, actions, and relationships, and avoids abstraction, metaphysics, and apocalypticism. Roberta Sabbath argues that a diverse array of Jewish artifacts, from sacred scripture to contemporary novels and ballet performance, articulate a tradition that has existed for millennia in mythic, proto-historic, legalistic, mystical, philosophical, and aesthetic expressions of Jewishness. The author refers to this tradition as Jewish literary illumination, and she deftly demonstrates how it illuminates the most salient message of Judaism: that earthly existence and the body are also the site of the spiritual and the sacred.